The Role of Joint Audit in Reducing Cases of Financial Default in Banks Listed on the Iraq Stock Exchange - Raed Salman Al-Salhi , Yahya; Fadhil Khudhair Al-Tai , Bushra (Journal of Economics and Administrative Sciences, 2024)
The method of joint auditing is not a recent appearance, but it is needed at the present time due to the occurrence of many global problems and crises. The research problem was represented by the increasing cases of financial distress of economic units, especially the collapse of economic units that occurred in the recent global crises. The research was based on the hypothesis that applying The method of joint auditing in economic units helps in reducing cases of financial distress, as the research aimed to measure the extent to which joint auditing can reduce the occurrence of cases of financial distress in economic units listed on the Iraq Stock Exchange. The research included 14 private banks listed on the Iraq Stock Exchange. Iraq Securities Exchange as a sample for a period of ten years from 2011 to 2020. The research used the survey method to measure the application of the joint audit method, and used the KIDA model to measure financial distress in the research sample. The most important results of the research were that financially distressed units decreased with the application of the joint audit method, that is, whenever there was a joint audit, the incidence of financial distress in economic units decreased.